Vision-based formation tracking with multiple mobile robots - Tan, Yi Hong (Nanyang Technological University, 2021)
In a multi-robot system, a team of robots share a similar goal and work together to complete the task more efficiently. Over these years, as more research were conducted on multi-robot system, the advantages became more obvious. Formation tracking was one of the key aspects in a multi robot system because an organized team reduces the probability of collision. Therefore, this project aimed to study the control algorithms of formation tracking with multiple mobile robots using vision-based sensors such as a camera. In this project, a vision-based detection method was developed using image processing techniques. This allows the robots to be able to detect objects and acquire data such as distance and relative angle using visual feedback. Thereafter, different control algorithms were designed to control 3 robots to move to their destination safely in a rigid formation. All experiments were conducted using simulations.